Effets d’un traitement antioxydant sur l’intoxication chronique à l’Aluminium « Etude expérimentale chez la souris » - DOUICHENE SALIMA (My University, 2016)
Chemicals with neurotoxic effects are found to be very different, citing the Aluminum. The versatility of Aluminum chemistry will ensure its burgeoning use in the future in all manner of applications. This very same chemistry will also ensure its increased biological availability in all biota including Man. We do not know enough about the biological chemistry of a chronic and sub-acute exposure to Aluminum to be able to predict its impact on human health. Although the hypothesis of a link between Aluminum and Alzheimer's disease (AD) has been supported by several epidemiological studies, there is much controversy regarding these findings and their interpretation. Nowadays, the toxicity of Aluminum is well established in the animal’s laboratory, and the neurotoxic effect is studies by means of behavioral tests, memory tests and histological and biological analysis. There is no doubt that the drugs discovered for neurodegenerative disease are far from ideal, there are no more than acetyl cholinesterase inhibitors, in fact alternative medicine could be moderate and protect nerves from neurotoxicity and AD. Several means were considered to fight against this severe health problems, including herbal medicine which is based on the effectiveness of the antioxidant on lesions induced by metals. Curcumin is one of strong medicinal species used to reduce the damage caused by aluminum, it is a powerful antioxydant that prove an oxidative stress effect against reactions cascade of neurofibrillary tangles. Our aims is to clarify the role of Curcumin with a fixative of absorption as a protective and therapeutic agent against neurodegenerative disorders and Alzheimer's disease induced by Aluminum (AlCl3) on the pyramidal cells in cerebral cortex and hippocampus of albino mice, by means of Two experiences realized with a different exposition of albino mice; sub-acute and chronic exposure with a different manner (Oral and IP) on Curcumin with a fixative of absorption and AlCl3.
Keywords: Aluminum toxicity; Curcumin; Antioxidant effect; Neurodegenerative disorders; Alzheimer’s disease; albino mice; AlCl3.